Measurement of the e+e- → Z → bb forward-backward asymmetry and the B0B0 mixing parameter using prompt leptons - Dova, María Teresa (1999)
The time-integrated <mtext>B</mtext>0<mtext>B</mtext><mtext>̄</mtext>0 mixing parameter and the forward-backward charge asymmetry in the process <mtext>e</mtext>+<mtext>e</mtext>−<mtext>→b</mtext><mtext>b</mtext><mtext>̄</mtext> are measured in hadronic Z events containing prompt muons or electrons, collected by the L3 experiment in the years 1990 to 1995. The total sample of 3.3 milion hadronic Z events with a mean centre-of-mass energy of 91.26 GeV yields: AbFB=0.0960±0.0066(stat.)±0.0033(sys.), χb=0.1192±0.0068(stat.)±0.0051(sys.). This asymmetry measurement together with measurements at energies away from the Z pole energy yield a pole asymmetry and corresponding effective electroweak mixing angle of: A0,bFB=0.1015±0.0064(stat.)±0.0035(sys.), <mtext>sin</mtext>2<mtext>θ</mtext><mtext>̄</mtext><mtext>W</mtext><mtext>=0.2318±0.0013</mtext>.